Attitudinal factors among elementary school teacher education students - Honest Ummi Kaltsum; Muhamad Taufik Hidayat (Institute of Advanced Engineering and Science, 2021)
In second or foreign language learning, attitudinal factors were one of the key factors that determine language success and achievement. In Indonesia, foreign language (English) has been taught since elementary school, however research showed most Indonesian language learners in English showed unsatisfactorily result. This research aimed at disclosing the students’ attitudinal factors in learning foreign language by exploring their first experience in learning foreign language. This qualitative study employed exploratory case study design to interview students’ attitudinal factors by exploring the students past experience at first time learning foreign language. These students were from different education unit background when they were in elementary school. This study applied thematic analysis to interpret and analyze the data. The findings showed in case of attitudinal factors were categorized into three components that were cognitive, affective, and behavior. In case of cognitive and affective components, those who had good experiences felt happy in their first experience in foreign language and the vice versa. However, both were having similar learning behavior when they serve as an English teacher, they adopted particular learning behavior that was able to make students enjoy the foreign language learning.